Prevalence of White Spot Lesion during Orthodontic Treatment with Fixed Appliance (Update Dental College Journal, 2019)
Background: White spot lesions (enamel demineralization) is one of the most common and a significant risk associated with orthodontic treatment.Objective: To determine the prevalence of white spot lesion during fixed orthodontic treatment.Method: This prospective observational study and was conducted in the Department of Orthodontics and Dentofacial Orthopedics from January 2016 to December 2017 over a period of two years. Patients with fixed orthodontic appliance age between 12-30 years of both sex attended for follow up were included in this study. After taking written consent, a questionnaire included socio-demographic data, clinical and outcome variables including routine clinical photographs to examine WSL were filled up for each patient. Routine clinical photographs to examine WSL were taken after 6 months and 12 months of fixing orthodontics appliance. Qualitative data were expressed as frequency distribution and percentage.Results: Maximum patients were in age group 12 – 16 years and prevalence of WSL was also sought maximum in this group. Out of 36 cases with WSL, 14 (38.9%) were male and 22 (61.1%) were female. Prevalence of WSL after six month of fixing orthodontic appliance was 21.8% and 26.1% after 12 months. Prevalence of WSL after six month of fixing orthodontic appliance in male was 26.4% & in female was 19.6% and after 12 month of fixing orthodontic appliance it was 30.2% in male and 24.1% in female. After six months of fixing orthodontic appliance 1-3 WSLs was found in 17.0% cases and ≥ 4 WSLs in 4.8% cases. After twelve months of fixing orthodontic appliance 1-3 WSLs was found in 19.4% cases and ≥ 4 WSLs in 6.7% cases. Maximum WSL was found in maxillary incisors.Conclusion: This study showed that 21.8% of the study subjects developed white spot lesions during orthodontic procedure and incisors were the most common affected teeth.Update Dent. Coll. j: 2019; 9 (2): 40-42